O pensamento complexo de Edgar Morin: subs??dios te??ricos para a supera????o da fragmentada forma????o do professor de educa????o f??sica - Pereira, Dimitri Wuo (2017)
The graduation in Physical Education was influenced by its military, hygienic and sportive origins in Brazil. From the 80???s, it???s received some changing from the scientific thought that was established in the area. However, Physical Education does not always prepare the professional to face the challenges of acting in the school, perhaps for the academic graduation is surrounded of theories that do not dialogue to each other. It can be said that are so many strands which many teachers unaware or partially understand them. This issue creates a fragmentation of the knowledge, reducing the Physical Education conceptions to certain paradigms. If there was improvement in the theoretical foundation, since the end of the twentieth century, there still remains a lack of articulation among the knowledge, causing the disintegration of the sense of Physical Education at school and the depreciation of the teacher. It is believed that weaving the knowledge in the chain is a necessity to the teacher understand better his role at school; and, his specific contribution in the formation of children and young. Edgar Morin, with his complex thought, criticizes this scientific attitude that separate the knowledge without, promoting the dialogue of ideas, the perception of the whole and the parts, and the complementary perspective between opposite thoughts. Thus, the complexity is the basis that is going to support the argumentation, in which the theoretical character with an educational praxis view, therefore it believes in the process of action-reflection-action, as a promoter of the thought reformulation from the reality of the graduation, avoiding idealization and universalization to knowledge. It was the purpose of this thesis, discussing these theories and point out a possible way to the graduation of teachers. This paper ends showing that the Physical Education is not reducible to one essence and it has four principles that create knowledge which should be articulated: the movement, the life, the culture and the humanity. These pillars are the starting points that should be understood by the students as recursive form, that is, a pillar influences the other adding some values that were not in it before. It is believed that graduation can be developed like a game, whereby beginning with any pillar it is possible to reach in the others the opposite and complementary that will allow new debates, looks and proposals to solve the complex problem that is to educate. This knowledge game can add very much to the teacher graduation, because it allows navigate by the ocean of uncertainties of Physical Education knowledge passing through the island of certain which produced important knowledge to the teachers. This will make it possible to walk more confident in your professional practice.